Fragmented Digital Forensic Standards in Indonesian Criminal Evidence: Standar Digital Forensik yang Terfragmentasi dalam Pembuktian Pidana Indonesia - Claudia Agatha; R. Rahaditya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid expansion of information and communication technology has transformed criminal activities from physical to digital domains, positioning electronic data as a central element in criminal proceedings. Specific Background: Within this shift, digital forensics functions as a scientific mechanism to ensure the authenticity, integrity, and reliability of electronic evidence in legal processes under Indonesian law. Knowledge Gap: Despite normative recognition of electronic evidence, Indonesia lacks a comprehensive procedural framework governing digital forensic practices, particularly in the acquisition, analysis, and preservation of digital evidence. Aims: This study aims to analyze the legal framework and the role of digital forensics in criminal evidence from the perspective of Indonesian positive law using a normative juridical approach. Results: The findings reveal that digital forensic regulation remains fragmented and has not developed into an integrated procedural legal regime, resulting in reliance on expert testimony without binding standardized procedures and creating potential legal uncertainty. Novelty: This study highlights digital forensics as an epistemological bridge between technical facts and juridical construction while exposing structural limitations in the conventional criminal evidentiary system. Implications: The absence of clear procedural standards underscores the need for a more systematic legal framework to ensure certainty, consistency, and reliability in digital evidence within Indonesia’s criminal justice system. Highlights: Regulatory structure remains partial and lacks integrated procedural rules. Evidentiary strength depends heavily on expert interpretation without binding standards. Absence of clear mechanisms creates uncertainty in courtroom validation processes. Keywords: Digital Forensics, Criminal Evidence, Normative Juridical Approach.